Sport activities for children and adolescents: the Position of the European Academy of Paediatrics and the European Confederation of Primary Care Paediatricians 2023—Part 1. Pre-participation physical evaluation in young athletes - Turska-Kmieć, Anna; Neunhaeuserer, Daniel; Mazur, Artur; Dembiński, Łukasz; del Torso, Stefano; Grossman, Zachi; Barak, Shimon; Hadjipanayis, Adamos; Peregud-Pogorzelski, Jarosław; Kostka, Tomasz; Bugajski, Andrzej; Huss, Gottfried; et al. (Frontiers in Pediatrics, 2023)
The European Academy of Paediatrics (EAP) and The European Confederation of Primary Care Paediatricians (ECPCP) emphasize the importance of promoting healthy lifestyles within the paediatric population. Many health professionals have questions concerning adequate levels of physical activity (PA) for both the healthy paediatric population and for those who may have specific complications. Unfortunately, the academic literature that provides recommendations for participation in sports activities within the paediatric population that have been published during the last decade in Europe is limited and are mainly dedicated to specific illnesses or advanced athletes and not towards the general population. The aim of part 1 of the EAP and ECPCP position statement is to assist healthcare professionals in implementing the best management strategies for a pre-participation evaluation (PPE) for participation in sports for individual children and adolescents. In the absence of a uniform protocol, it is necessary to respect physician autonomy for choosing and implementing the most appropriate and familiar PPE screening strategy and to discuss the decisions made with young athletes and their families. This first part of the Position Statement concerning Sport Activities for Children and Adolescents is dedicated to healthy young athletes.